Association between low-dose pulsed intravenous cyclophosphamide therapy and amenorrhea in patients with systemic lupus erythematosus: A case-control study - Kanno Tokiko; Sugiura Tomoko; Gono Takahisa; Kawaguchi Yasushi; Katsumata Yasuhiro; Baba Sayumi; Hara Masako; Yamanaka Hisashi (BMC, 2011)
Abstract Background The risk for amenorrhea following treatment of systemic lupus erythematosus (SLE) patients with low-dose intravenous cyclophosphamide (IVCY) has not been fully explored. Our objective was to ascertain the incidence of amenorrhea following treatment with low-dose IVCY and the association between amenorrhea and the clinical parameters of SLE. Methods A case-control retrospective study of premenopausal women ≤ 45 years old who had been treated for SLE with low-dose IVCY (500 mg/body/pulse) plus high-dose glucocorticoids (0.8-1.0 mg/kg/day of prednisolone; IVCY group) or glucocorticoids alone (0.8-1.0 mg/kg/day of prednisolone; steroid group) in our hospital from 2000 through 2009 was conducted using a questionnaire survey and medical record review. Results Twenty-nine subjects in the IVCY group and 33 subjects in the steroid group returned the questionnaire. A multivariate analysis revealed that age at initiation of treatment ≥ 40 years old was significantly associated with amenorrhea [p = 0.009; odds ratio (OR) 10.2; 95% confidence interval (CI) 1.8-58.7]. IVCY treatment may display a trend for association with amenorrhea (p = 0.07; OR 2.9; 95% CI 0.9-9.4). Sustained amenorrhea developed in 4 subjects in the IVCY group and 1 subject in the steroid group; all of these patients were ≥ 40 years old. Menses resumed in all subjects < 40 years old, irrespective of treatment. Conclusions Although low-dose IVCY may increase the risk for amenorrhea, our data suggest that patients < 40 years old have a minimum risk for sustained amenorrhea with low-dose IVCY treatment. A higher risk for sustained amenorrhea following treatment with IVCY is a consideration for patients ≥ 40 years old.